THE IMPLEMENTATION OF SCHOOL PRINCIPALS’ LEADERSHIP IN ENHANCING TEACHER PERFORMANCE AND CAREER INTEREST IN ELEMENTARY SCHOOLS IN SUMBER HARTA DISTRICT, SOUTH SUMATRA - Moh. Rofiq; Iis Siti Aisyah; Lud Waluyo (RADJA PUBLIKA, 2025)
School principal leadership plays a critical role in improving the quality of education, particularly in supporting teacher performance and career development. However, challenges such as the aging of teachers nearing retirement, limited technological resources, and administrative burdens often hinder the effective implementation of leadership. This study aims to analyze the influence of school principal leadership on the performance and career interest of elementary school teachers in Sumber Harta District, South Sumatra. A qualitative research method with a case study approach was employed. Data were collected through interviews, observations, and document analysis involving school principals and teachers as informants. The data analysis process included data reduction, data presentation, and conclusion drawing. The findings indicate that principals provide support through supervision, training, informal motivation, and access to information related to teacher certification. A total of 80% of teachers reported that school leadership improved their performance, while 75% expressed similar sentiments regarding career development. Nevertheless, issues related to teacher age and the limitations of technological infrastructure remain significant obstacles.